PENERAPAN OPERASI HIMPUNAN DAN FUNGSI AGREGASI PADA PERANCANGAN BASIS DATA ALUMNI UNIVERSITAS HALU OLEO - Aswani Aswani; Natalis Ransi; Rahmat Ramadhan (Informatics Engineering Department of Halu Oleo University, 2018)
Halu Oleo University is building an integrated university database with a centralized database system. One of the data that is integrated is the alumni database. The alumni database can be designed using a relational database system. According to [1] the relational database can be an alternative because it has the advantage of storage capacity. Some basic mathematical theories such as set operations can be used to design and develop a database. Furthermore, the agreement function can be used to retrieve information from a database. In this research will be done on the database design alumni of Halu Oleo University by applying the approach of set operation and aggregation function.Keywords— Set Operation, Aggregation Function, Alumni DatabaseDOI : 10.5281/zenodo.1343370